(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2017)
The indigenous struggle in Nicaragua has a nuanced history. Mention indigenous peoples, and the first names that occur in people’s imaginary are Subtiava, Monimbó and the ethnic groups of the Caribbean Coast. This article discusses one of the possibly oldest groups, one without a clear ethnic origin. Located in the North Central part of the national territory, the Matagalpa as an indigenous people possess a community organizational structure, which functions with two authorities, one traditional and the other administrative. Both exercise a leadership function, which articulates political-administrative work and channels it in territories through the traditional authority following its statutes. The Matagalpa culture is one of the most important in the historical development of the Nicaraguan territory. Often known as the Archer Indians, this group has a long history of rebellion and insurgency including diverse armed actions in defense of its rights. As such the bow and arrow have become symbols of territorial resistance and defense. Currently, the struggle for land, respect and recognition of its belief system, as well as incursion into decision-making in local governments are demands carried out by the indigenous people as a historic commitment to each indigenous woman and man. In the local context, mestizo citizens continue to misunderstand the indigenous identity and discriminate against this ethnic identity. To be an indigenous leader is unacceptable for the centers of local power, so families toughen their resolve to struggle for the consolidation of a united front and maintain indigenous resistance with mechanisms of leadership and governance in each territory for common well-being. Raíces - Revista Nicaragüense de Antropología. Año 1 No. 1/2017: 105-117